EFFECTS OF ORGANIC MANURE ON GROWTH PERFORMANCE OF Azadirachta indica (A. JUSS) SEEDLINGS DURING EARLY GROWTH IN THE NURSERY - Jibo, A. U.; Salami, K. D.; Inuha, I. M. (FUDMA JOURNAL OF SCIENCES, 2023)
Seedling production in the forest nursery is very inevitable; therefore, there is need to examine fertilizer on seedlings growth in preparation for plantation in the growing season. A research investigated the effect of poultry manure treatment at different levels on the growth and early performance of Azadirachta indica (Neem) seedlings. Soils used for the experiment were collected from study area. The seeds collected on the ground were distributed and planted at the same proportion of sand but different ratio of poultry manure. Experiment had four (4) treatments in which each them had the same proportion of river and top soil but different ratio of poultry manure:T1(1:1:2), T2(1:1:3),T3(1:1:4) and T4(1:1) control respectively. Complete Randomized Design (CRD) was used for this research with four (4) treatments and five (5) replications making twenty (20) samples all together. The growth parameters measured include: number of leaves, stem diameter and growth height. Analysis of variance showed that there were no significant difference (p<0.05) among the growth of Neem subjected to poultry manure at different treatments sown in all parameters. T3 had the highest growth height with mean value of 25.40cm followed by T2 with 23.70cm. Also, T1 had the best mean value of stem diameter with 4.38mm followed by T2 with 4.36mm while the least is the control. The treatments with highest mean number of leaves were T1 and T3with 76.60 followed by T2 with 69.00. T4 had the lowest value with 54.80. The result showed the slight variation in shoot height of